PENGARUH MODIFIKASI PERMAINAN BOTOLKARET TERHADAP KEMAMPUAN PASSING DAN MINAT SISWA PADA PEMBELAJARAN SEPAK BOLA - Aris Wiji Saputra; Wahyu Setia Kuscahyaning Putri; Benny Widya Priadana (Jurnal Porkes, 2026)
Soccer instruction is often hindered by students’ low interest in learning and poor basic motor skills, particularly in the technique of inside-foot passing, due to a lack of instructional variety. This study aims to determine the effect of a modified rubber bottle game on students’ inside-foot passing ability and interest in learning during soccer instruction. A quantitative method with a one-group pretest-posttest design was used. A sample of 42 ninth-grade students from MTs Ulumiyah Kebonharjo was selected using purposive sampling. The research instruments consisted of a passing skill test and a learning interest questionnaire. Data were analyzed using the Shapiro-Wilk normality test and a paired-sample t-test with SPSS version 23. The results of the study indicate that the modification of the rubber bottle game does not have a significant effect on inside-foot passing ability (Sig. 0.971 > 0.05), but has a highly significant effect on students’ learning interest (Sig. 0.000 < 0.05). In conclusion, the modification of the rubber bottle game is effective in increasing learning interest but has not yet been able to significantly improve passing ability; therefore, it needs to be combined with more structured technical training.